A Rare Case of Retroperitoneal Leiomyoma - Rajiv Mahendru; Geetinder Gaba; Shweta Yadav; Gurmeet Gaba; Chinky Gupta (Case Reports in Surgery)
Introduction. Leiomyoma uteri is one of the most common benign conditions for which women undergo hysterectomy every year. Fibroids found retroperitoneally are a rare entity, especially, primary retroperitoneal fibroid. Case Presentation. We report a case of 42-year-old para 1 who presented to our hospital with recurring retention of urine, lower abdominal and pelvic pain, and dyspareunia . Provisional diagnosis on the basis of examination and imaging was large subserosal fibroid with mild right-sided hydroureteronephrosis, due to pressure effect of the fibroid. Abdominal hysterectomy was done for the patient, and intraoperatively, a bulky uterus was found with multiple small fibroids on anterior and posterior walls, and a large fibroid approx. 10×8 cm was found arising from the posterior surface at the level of internal os retroperitoneally, which was confirmed by histopathology as leiomyoma. Conclusion. Retroperitoneal fibroids are rare neoplasms and treatment is surgical removal. Preoperative imaging can only give provisional diagnosis and can be misguiding. Final diagnosis of retroperitoneal fibroid can be made only intraoperatively.